2018
DOI: 10.1186/s12885-018-5121-z
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in long-term adjuvant endocrine therapy adherence and mortality among Medicaid-insured breast cancer patients in Texas: Findings from TCR-Medicaid linked data

Abstract: BackgroundThere are racial/ethnic disparities in breast cancer mortality may be attributed to differences in receipt of adjuvant cancer treatment. Our purpose was to determine whether the mortality disparities could be explained by racial/ethnic differences in long-term adherence to adjuvant endocrine therapy (AET).MethodsWe conducted a retrospective cohort study with the Texas Cancer Registry and Medicaid claims-linked dataset of women (20-64 years) diagnosed with local and regional breast cancer who filled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 48 publications
(60 reference statements)
1
35
1
Order By: Relevance
“… TAM & AI. N = 19551 Implementation PDC≥ 80% Year 1: 76.4%, Year 2: 72.1%, Year 3: 68.4%, Year 4: 65.7%, Year 5: 58.5% 1) Asian/Pacific Islander ethnic groups 1) Hispanic 2) Black Farias, 2018 (US) [ 41 ] Retrospective cohort. Regional Cancer Registry and Medicaid claims database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… TAM & AI. N = 19551 Implementation PDC≥ 80% Year 1: 76.4%, Year 2: 72.1%, Year 3: 68.4%, Year 4: 65.7%, Year 5: 58.5% 1) Asian/Pacific Islander ethnic groups 1) Hispanic 2) Black Farias, 2018 (US) [ 41 ] Retrospective cohort. Regional Cancer Registry and Medicaid claims database.…”
Section: Resultsmentioning
confidence: 99%
“…The completeness and reliability of data source for 15 studies were considered to be good, with multiple databases linked together at national or regional level. Studies that used databases from private insurance or healthcare systems [ 34 , 40 , 41 , 46 , 47 ] and hospital or pharmacy databases without linkage to other databases [ 30 , 38 , 42 ] were rated as intermediate quality. One study was considered to have poor data source, as information was based on survey and incomplete data collection from medical charts [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Endocrine therapy is typically recommended for at least five years. While we were not able to study drug adherence in our patients, unsatisfactory adherence to treatment for the entire recommended duration is known to be associated with worse survival, which could potentially explain the observed increasing mortality rate among treatment-compliant patients in our study 28 . As such, the survival benefit of endocrine therapy compliance would better reach its full potential if common factors contributing to non-adherence, such as patient forgetfulness and concerns about adverse effects, were followed up and addressed 29 .…”
Section: Treatment Compliance and Overall Survival The High Mortalitmentioning
confidence: 88%
“…Racial differences have been found in the adherence to adjuvant ET to impact survival among breast cancer patients [105] (Table 2). Some found that the racial disparity in luminal breast cancer survival is unrelated to differences in tumor stage or therapy initiation but rather to differences in tumor biology that may render them less responsive to ET [9].…”
Section: Factors Impacting Luminal Breast Cancer Survival With Respec...mentioning
confidence: 99%